2011
DOI: 10.1371/journal.pone.0016536
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Epidermal Growth Factor Interaction with Four Different Cell Lines: Intriguing Effects Imply Strong Dependency of Cellular Context

Abstract: The interaction of the epidermal growth factor (EGF) with its receptor (EGFR) is known to be complex, and the common over-expression of EGF receptor family members in a multitude of tumors makes it important to decipher this interaction and the following signaling pathways. We have investigated the affinity and kinetics of 125I-EGF binding to EGFR in four human tumor cell lines, each using four culturing conditions, in real time by use of LigandTracer®.Highly repeatable and precise measurements show that the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 21 publications
(24 reference statements)
3
57
0
Order By: Relevance
“…There the ligand is EGF, and the messenger is associated with calcium signaling and is able to pass through gap junctions; one possibility is inositol 1,4,5-trisphosphate (IP3). The cell size is a ∼ 10 μm, the dissociation constant is as small as (33), the dissociation rate is μ ∼ 0.001 s −1 (34), and the EGF diffusion constant is D ∼ 50 μm 2 s −1 (35). The turnover rate of IP3 is estimated as ν ∼ 0.1 s −1 (36).…”
Section: Discussionmentioning
confidence: 99%
“…There the ligand is EGF, and the messenger is associated with calcium signaling and is able to pass through gap junctions; one possibility is inositol 1,4,5-trisphosphate (IP3). The cell size is a ∼ 10 μm, the dissociation constant is as small as (33), the dissociation rate is μ ∼ 0.001 s −1 (34), and the EGF diffusion constant is D ∼ 50 μm 2 s −1 (35). The turnover rate of IP3 is estimated as ν ∼ 0.1 s −1 (36).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the kinetic behavior of the EGF-EGFR interaction may vary greatly among cell lines (14), as demonstrated by real-time interaction measurements performed using LigandTracer ® instruments. The binding curves showed at least two parallel interaction events, one fast-on-fast-off interaction and one higher affinity interaction, in which the association and dissociation rates of EGF were much slower.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have demonstrated that the presence of gefitinib affects the kinetic properties (association and dissociation rates) of the EGF-EGFR interaction in certain cell lines, observed as an increase in affinity (10,14). This observation may be the result of the larger number of EGFR dimers present on the cell surface upon gefitinib treatment, regardless of their kinase activity.…”
Section: Introductionmentioning
confidence: 98%
“…LigandTracer Yellow was used for 131 I-cetuximab and Affibody molecule 111 In-Z342 measurements, and LigandTracer Grey for 125 I-trastuzumab measurements, all according to previously published protocol (3). After a short baseline measurement, the cells were incubated first at a lower concentration of protein, then at a higher concentration and finally the cells were put in fresh cell culture medium to monitor the release of bound material.…”
Section: Real-time Interaction Measurements In Ligandtracermentioning
confidence: 99%